An Unexplored Strategy for Synthesis of Zno Nanowire Films by Electrochemical Anodization Using an Organic-Based Electrolyte. Morphological and Optical Properties Characterization - Sanchez-Poblete, J; Boulett-Neira, A; Boulett-Neira, A (Elsevier B.V., 2021)
In this work we report the preparation of ZnO nanowires by an unexplored strategy of electrochemical anodization using an electrolyte medium based mainly on ethylene glycol and fluoride ions, studying the anodization as a function of parameters, such as: temperature and voltage. The results obtained by field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) show mainly a nanowire morphology with an average length of 296 nm. Microscopic evidence demonstrate that the size of nanostructures, morphology and homogeneity of resulting surfaces are completely related to the temperature and voltage conditions used during the zinc anodization. The results obtained by Raman spectroscopy and X-ray diffraction (XRD) corroborate the formation of only ZnO, with a crystallographic structure of hexagonal wurtzite. Finally, through diffuse reflectivity spectroscopy, bandgap values of [3.19–3.22] eV were estimated, classifying it as a material with potential characteristics for the fabrication of photoelectrodes for photoelectrochemical and photocatalytic applications. © 2021 Elsevier B.V.